Community Empowerment Through Potato Dodol Processing to Increase Family Income in Kerinci District - Santri Nurhalima, Afdila; Syur'aini, Syur'aini (Universitas Negeri Padang, 2023)
Kerinci Regency is an area that produces a variety of agricultural products. In Lubuk Nagodang Village, Siulak District, people convert various agricultural products into raw materials for home industries. One of them is processing potatoes into potato dodol. Starting in 1994 in Lubuk Nagodang Village, this business developed rapidly by involving the community in Family Empowerment and Welfare (PKK) groups. The positive impact of the potato dodol business on socio-economic empowerment is that it opens up opportunities for the people of Lubuk Nagodang Village to increase their income. The potato dodol produced includes a variety of flavors, demonstrating product diversification as the key to consumer appeal. Empowerment is carried out through education, training and government policies, by presenting the Kerinci Regency Regional Superior Product Determination. This business not only produces delicious local products, but also drives the economic empowerment of local communities through active involvement in production and support from the local government. The suggestion in this research is that in empowering the Dodol Potato Business, it is recommended that the Department of Cooperatives and Manpower carry out continuous monitoring, so that the development of Dodol Potatoes, both in terms of product innovation and marketing, can be achieved optimally.